Decomposition analysis of anxiety symptom differences between urban and rural Chinese university students: cross-sectional study - Tuersun, Yusupujiang; Xie, Yuying; Zhou, Qingping; Yu, Yao; Wang, Wenyu; Wang, Chenxi; Liu, Siyuan; Song, Yuyao; Liang, Zhenning; Qian, Yi (Frontiers in Psychiatry, 2025)
BackgroundAnxiety is a prevalent psychological disorder characterized by excessive worry and fear, which significantly impacts the mental health of university students. Anxiety symptoms are often misunderstood, leading to delays in seeking help. This issue is particularly notable among college students, who may experience anxiety due to academic pressures, societal expectations, and family issues. This study explores anxiety symptoms among urban and rural Chinese university students, aiming to analyze the differences and contributing factors. The primary goal of this study is to analyze the differences in anxiety symptoms between urban and rural Chinese university students and to decompose these differences into the contributions of various individual and socio-economic factors using the Fairlie decomposition model.MethodsA cross-sectional survey was conducted between January and February 2023, involving 7,230 valid questionnaires from undergraduate students across ten provinces in China. The Generalized Anxiety Disorder 7 (GAD-7) scale was used to assess anxiety symptoms. Demographic characteristics, academic performance, lifestyle factors, depressive symptoms (Patient Health Questionnaire-9; PHQ-9), and eHealth (SeHealth Literacy Scale) literacy were controlled for as covariates. The Fairlie decomposition model was applied to examine the contributing factors to the observed differences in anxiety symptoms between urban and rural students.ResultsThe study found that 38.91% of students reported experiencing anxiety symptoms. The prevalence was higher among rural students (40.2%) compared to urban students (36.8%). Significant factors contributing to this difference included depressive symptoms (51.07% contribution), exercise habits (7.07% contribution), and family income levels. Rural students were found to be at higher risk for anxiety symptoms, with those from lower-income families and those lacking exercise habits exhibiting greater anxiety.ConclusionThe results demonstrate a significant difference in anxiety symptoms between urban and rural college students in China. The disparity is mainly influenced by depressive symptoms, exercise habits, and family income. The findings suggest the need for tailored mental health interventions for rural students, with a focus on improving access to resources, promoting physical activity, and addressing socio-economic factors. The study underscores the importance of considering urban-rural differences in the development of effective mental health strategies for university students.